PENGARUH KUALITAS PELAYANAN PCARE TERHADAP KEPUASAN PASIEN RAWAT JALAN DI UPT. PUSKESMAS PAGAR JATI - Marudin, Mangapoh Ferry; Kasim, Felix; Gurusinga, Rahmad (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
PHC as one of the government facilities has a very strategic role in accelerating the improvement of public health status. A positive attitude towards the services of these two parts will be built if the services received by the community are in accordance with or even exceed their wishes. This will affect the public's perception of being loyal so that they will return to the health center. Service Quality (SerQual) is a multi-dimensional measure used to measure public perceptions of service quality. Service Quality consists of five dimensions, namely Tangibles, Reliability, Responsiveness, Assurance (Communication, Credibility, Courtesy), and Empathy. The quality of this service is further facilitated by one of the applications issued by the Social Security Administering Body (BPJS) in the health sector, namely Primary Care (PCare). With BPJS PCare, it is hoped that it can provide convenience and quality health services, especially in the Registration and Outpatient sections. This study aims to examine the effect of service quality on outpatient patient satisfaction in the PCare section or registration at UPT. Jati Fence Health Center. This type of research is quantitative research with explanatory research methods. The results of research that has been carried out on 100 samples as users of outpatient facilities, it turns out that there is a significant relationship between service quality and outpatient patient satisfaction in the PCare Department at UPT. Pagar Jati Public Health Center in 2023.